PREVALENS KETERLAMBATAN PERKEMBANGAN ANAK DI TAMAN KANAK-KANAK SABANA SARI, DENPASAR BARAT - Widiaskara, Luh Gede Ayu Putri Vebriany; Windiani, I Gusti Ayu Trisna (E-Jurnal Medika Udayana, 2017)
The incidence of general children delayed development is 10 % worldwide. Therefore, early screening on children development is important to detect early delayed development. One example of screening technique that used worldwide is Denver II. Descriptive cross-sectional design was use to determine prevalence of delayed development and influencing factors in Sabana Sari Kindergarten. Sample data was collected by using Denver II skrining tools and questionnaire to children aged 4-6 years old through total sampling technique. From 89 sampels, there are 32 (36%) have normal result, 55 (61,8%) have suspect result, and 2 (2,2%) have untestable result. Based on questionnaire that given to 89 research subject and then analyzed by Chi-square found that education of mother (p= 0.025) give a significant result on Denver II result. From this study can be concluded that most of childrens in Sabana Sari Kindergarten were found had delayed development (61,8%) and only education of mother (p= 0.025) give a significant result on Denver II result. Keywords: delayed development, screening technique, Denver II, influencing factors